The effect of using mycotoxin binder on daily body weight gain, protein consumption, and feed protein efficiency in broilers exposed to mycotoxins - Alfanindya, Evita Aisyah; Al-Arif, Mohammad Anam; Yunus, Muchammad; Safitri, Erma; Warsito, Sunaryo Hadi; Utama, Suzanita (Jurnal Agro Veteriner, 2025)
This research was an experimental study using completely randomized design (CRD) using 24 male broiler chickens randomized with 4 treatments with each treatment consisting of 6 broiler chickens. C was the control treatment consisting only commercial feed. P1 treatment was the addition of commercial feed, aflatox in and ochratoxin with the amout of 1 mg/kg feed for each. P2 treatment was the addition of commercial feed, aflatoxin with the amount of 1 mg/kg feed, ochratoxin 1 mg/kg feed, and and toxin binder as much as 1.1 g/kg feed. P3 treatment was the addition of commercial feed, aflatoxin with the amount of 1 mg/kg feed, ochratoxin 1 mg/kg feed, and and toxin binder as much as 1.6 g/kg feed. The result showed that P2, control and P3 treatment have the highest average daily gain. The highest to lowest protein cons umption showed in following order P1, P3, C, P2 treatment. P2 treatment have the highest protein efficiency showed by having the highest average daily gain with less production cost. Mycotoxin binder given in feed contaminated with aflatoxin and ochratoxin can help to reduce the negative effect of mycotoxin as to in creasing protein consumption and average daily gain